Complex Substrate Leading to PVC-Mediated Systolic Dysfunction in addition to Sustained Monomorphic VT in Repaired Tetralogy of Fallot - Cosmin Cojocaru; Silvia Deaconu; Viviana Gondos; Sebastian Onciul; Ioana Petre; Oana Gheorghe-Fronea; Radu Vătășescu (Diagnostics, 2024)
Frequent premature ventricular complexes (PVCs) are associated with deleterious effects on left ventricular (LV) function in various clinical scenarios. Repaired tetralogy of Fallot (rTOF) is frequently affected by sustained ventricular arrhythmias dependent on complex post-surgical substrates. However, there is limited data regarding the potential of arrhythmogenic isthmuses to generate frequent PVCs and PVC-mediated LV systolic dysfunction development in rTOF. We present a case of rTOF experiencing relatively infrequent episodes of internal shocks for episodes of sustained monomorphic ventricular tachycardia and a high burden of PVCs associated with left ventricular systolic function deterioration, in which the successful substrate ablation of the anatomical VT isthmuses also led to PVC abolition and consequently to LV systolic function normalization. In such cases, understanding the pathogenic mechanisms that lead to LV dysfunction is only possible by rigorous clinical reasoning, which leads to a tailored specific treatment.